Aluminium trihydroxide: Novel reinforcing filler in Polychloroprene rubber. (6th December 2017) - Vijayan, Dhanya; Mathiazhagan, A.; Joseph, Rani
Abstract: Aluminium trihydroxide (ATH) nano particles with rod like morphology were incorporated in Polychloroprene (CR) rubber by melt mixing method, to prepare nanocomposites with enhanced mechanical, thermal, sorption and dielectric properties. The effect of ATH loading on various properties of the nanocomposites was studied and the results were correlated with the microstructure of the composites using TEM, SEM and XRD analysis. Tensile strength and modulus were found to be improved by the addition of ATH, the enhancement in former being 27% at 10 phr of ATH loading. The incorporation of ATH improved the thermal stability with an increment of up to 31 °C in the maximum degradation temperature. Differential scanning calorimetry studies show marginal increase (3 °C) in glass transition temperature (Tg ) at 10 phr of ATH. Dynamic mechanical studies indicate agglomeration of ATH particles at higher loadings. The experimentally obtained storage modulus values have been compared with theoretical prediction, using different composite reinforcement models. The transport properties and dielectric permittivity of the composites registers enhancement with the addition of ATH. The improvement in properties by the addition of ATH is attributed to the polar-polar interaction between the matrix and filler particles. The present study confirms that ATH can be an effective reinforcing filler for CR matrix. Graphical abstract: Highlights: The effect of ATH on the properties of CR-ATH nanocomposites studied. Improvement in mechanical, thermal, barrier and dielectric properties of the composite. Better correlation between SEM, TEM, and mechanical properties. ATH can be used as a reinforcing filler in CR.